2018
DOI: 10.1177/1071100718786166
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-Octyl Cyanoacrylate Topical Skin Adhesive and Simple Interrupted Nylon Sutures for Wound Closure in Ankle Fracture Surgery

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…This is in contrast to a number of other studies in both orthopedic and other surgical specialty settings, which report that application of TSA is quicker than suturing. 21,22 Given this time difference is a very small percentage of the overall operative time, we do not think this finding is clinically relevant. A number of studies report concerns over wound dehiscence 3 and inflammation when using TSA, which was also found in this study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This is in contrast to a number of other studies in both orthopedic and other surgical specialty settings, which report that application of TSA is quicker than suturing. 21,22 Given this time difference is a very small percentage of the overall operative time, we do not think this finding is clinically relevant. A number of studies report concerns over wound dehiscence 3 and inflammation when using TSA, which was also found in this study.…”
Section: Discussionmentioning
confidence: 91%
“…There is extremely limited evidence regarding the use of TSA vs sutures in foot and ankle surgery. Park et al 22 retrospectively investigated the use of topical skin adhesive compared to nylon sutures in ankle fracture surgery and found that use of TSA was quicker and had higher patient satisfaction rates, although there was a higher (but not statistically significant) increase in wound dehiscence. Park et al 21 also retrospectively reviewed sutures vs TSA in Achilles tendon surgery and found no difference in wound complications, but they did find operating time significantly longer with sutures and patient satisfaction significantly higher with TSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] For this reason, topical skin adhesives, which have the advantages of good scar cosmesis, infection prevention, easy skill acquisition, and lack of need for dedicated removal have begun to attract attention. [7][8][9][10][11][12][13] Liquid 2-octyl cyanoacrylate and n-butyl cyanoacrylate monomers are commonly used ingredients for topical skin adhesives because they polymerize into solid chains upon contact with the wound surface and hold wound edges together. 14 Although 2-octyl cyanoacrylate and n-butyl cyanoacrylate are harmless to most patients, they can act as allergens and cause allergic contact dermatitis (ACD).…”
Section: Introductionmentioning
confidence: 99%